Process and Product Innovation in the Spanish Construction Industry: The Mediating Role of Organizational Innovation - Rosa, Nuria; Villena, Francisco; González, Eloísa (International Journal of Industrial Engineering and Management, 2023)
Innovation in the construction industry is affected by the incorporation of new technologies that allow a change in the way of working in the Architecture, Engineering and Construction industry. The objective of this paper is to analyze the behavior of the main innovations (prod- uct, process and organizational) through a PLS model applied to the Spanish construction industry. The results applied to 257 companies indicate that organizational innovation exerts a mediating effect on the relationship between process and product innovation. Therefore, this research contributes to a better understanding of the innovative behavior of the Spanish construction sector and demonstrates the importance of managing a plan for organizational innovation. Article history: Received (June 12, 2022); Revised (December 14, 2022); Accepted (January 20, 2023); Published online (January 20, 2023)